Nonequilibrium carrier dynamics in transition metal dichalcogenide semiconductors. (12th August 2016) - Steinhoff, A; Florian, M; Rösner, M; Lorke, M; Wehling, T O; Gies, C; Jahnke, F
Abstract: When exploring new materials for their potential in (opto)electronic device applications, it is important to understand the role of various carrier interaction and scattering processes. In atomically thin transition metal dichalcogenide semiconductors, the Coulomb interaction is known to be much stronger than in quantum wells of conventional semiconductors like GaAs, as witnessed by the 50 times larger exciton binding energy. The question arises, whether this directly translates into equivalently faster carrier–carrier Coulomb scattering of excited carriers. Here we show that a combination of ab initio band-structure and many-body theory predicts Coulomb-mediated carrier relaxation on a sub-100 fs time scale for a wide range of excitation densities, which is less than an order of magnitude faster than in quantum wells.